Mulheres de seus corpos e de suas crenças: relações de gênero, práticas mágico-religiosas e Inquisição no mundo português (1541-1595) - Marcus Vinícius Reis (2018)
The starting point for this thesis was the finding that women made up the majority among the individuals who were prosecuted by the Portuguese Holy Office from 1541 to 1595, whose motivation consisted in the presumed diabolical pacts performed by these women and legally interpreted under the crime of witchcraft. This context corresponds to the first great wave of persecution carried out by the Portuguese Inquisition on magical-religious practices, interpreted by the inquisitors as belonging to the universe of witchcraft and relations with the Devil. Thus, this thesis intends to investigate how, during the period in question, some women prosecuted by the Office from the crime of witchcraft, performed their gender identities through the fame as witches that have been built throughout their lives, which made it possible for the Inquisition to reach their trajectories. The analyzes are based on thirteen processes, in which the defendants are: Beatriz Borges, Brites Frazão, Brites Marques, Catarina de Faria, Inacia Gomes, Ana Álvares (Ana do Frade), Clara de Oliveira, Margarida Lourenço, Simoa de São Nicolau, Maria Gonçalves, Margarida Carneiro Magalhães, Violante Carneiro and Felícia Tourinho. The hypothesis is that the construction of these identities enabled these women witches to build social recognition and relative spaces of autonomy, even if inserted in a largely misogynist and patriarchal context. In view of the chronological and geographical dispersion of these processes, the concept of Atlantic History - under the cis-Atlantic approach - is used in this work because it allows the understanding of the magical-religious practices under a connected view belonging to the Atlantic System, as well as the established links among these witches. Moreover, this thesis is anchored in the concept of gender, considering it as an important historical category capable of providing the researcher with an understanding that social practices in this context were marked by patterns of masculinity and femininity and by gender relations based on a compulsory heteronormativity. Following these theoretical and methodological choices, it is believed that this work will contribute to the analyzes interested in defining a closer look at the gender dynamics whose phenomenon of witchcraft, including its characters, might be intertwined.